Counting the Tiger's Teeth : An African Teenager's Story - Falola, Toyin (Book collections on Project MUSE., 2015)
Counting the Tiger's Teeth narrates a crucial turning point in Nigerian history, the Agbekoya rebellion ("Peasants Reject Poverty") of 1968-70, as chronicled by Toyin Falola, reflecting on his firsthand experiences as a teenage witness to history. Falola, the foremost scholar of Africa of this generation, illuminates the complex factors that led to this armed conflict and details the unfolding of major events and maneuvers. The narrative provides unprecedented, even poetic, access to the social fabric and dynamic cosmology of the farming communities in rebellion as they confronted the modernizing state. The postcolonial government exercised new modes of power that corrupted or neglected traditional forms of authority, ignoring urgent pleas for justice and fairness by the citizenry. What emerges, as the rural communities organized for and executed the war, is a profound story of traditional culture's ingenuity and strength in this epic struggle over the future direction of a nation. Falola reveals the rebellion's ambivalent legacy, the uncertainties of which inform even the present historical moment. Like Falola's prizewinning previous memoir, A Mouth Sweeter Than Salt, this engagingly written book performs the essential service of providing a way of walking with ancestors, remembering the dead, reminding the living, and converting orality into a permanent text.